(untitled) (Quinto Sol, 2013)
At the beginning of the 20th Century the ruling sector of the National State evidenced important fractures.The battle between those who were demanding the continuity of the excluding politic modality against those who were claiming for the opening of the political system was an important characteristic of evident breaks within conservatism. In the context of replacements and reformists rearrangements we locate Ezequiel Ramos Mexia, as an active intellectual, Minister of Agriculture (1901-1906) and National Public Constructions (1907-1913). His importance lies not only in his public trajectory but also in the corpus of ideas and projects that he posed during his political performance stated in his written production, in the debates at the National Congress and also in the dispute with National employees. His ideas reflect the dominant conceptions about order and progress, with a particular vision concerning public lands and the southern native peoples. His proposals about the qualification of new areas to settle immigrants, moving them further away from most populated areas (considered as an exposure to higher political agitation), concluded in a plan for Patagonia, which appears as an attempt of response, from an economic approach, to the so called “Social Affair”.